REPRESENTATIONS OF GENDER, HIERARCHY AND OTHER RELATIONSHIPS IN THE EMBROIDERIES PARACAS NECRÓPOLIS - Frame, Mary (2008)
This paper explores categories and relationships among a group of inter-related figures on embroidered textiles from the Necropolis of Wari Kayan on the Paracas Peninsula. The depictions of garments worn by the embroidered figures, and their correspondence with actual garments, are discussed first. The garment depictions reveal gender and possibly age categories among the figures, while the golden adornments that they wear suggest hierarchical relationships among the members of the group. Additional hierarchical relationships, which appear to correspond with a high-ranking lineage, are carried in patterns of figure repetition on several textiles that display multiple figure types. Pattern is a salient feature of the Paracas Necropolis embroideries, but it is often studied in isolation from iconography. This study indicates that patterns of color, symmetry, and figure repetition are aspects of the graphic code that reiterate or add to the structured relationships evident in the iconography.